Extensions of Jacobson's Lemma - Corach, Gustavo (2013)
Jacobson’s Lemma says that if a c ∈ A thenac − 1 ∈ A−1 ⇐⇒ ca − 1 ∈ A−1 which holds separately for the left and the right invertibles of A, as well as for the non zero-divisors of A. In this note, we generalize the identity above and many of its relatives from ca − 1 to certain ba − 1: specifically we will suppose aba = aca. Three special cases are of interest: the case b = c which will give Jacobson’s lemma; the case in which aba = aca = a in which both b and c are generalized inverses of a ∈ A; and the case aba = a^2 in which c = 1. This last case goes back to Vidav; in particular, Schmoeger shows that aba=a^2 holds if there are idempotents p = p^2 q = q^2 for which a = qp and b = pq. The central results in this note are of course pure algebra: but in the neighboring realm of topological algebra they have very close relatives, and we take the opportunity to extend our purely algebraic observations to their topological analogues.